Evaluation of two commercial methods for rapid detection of the carbapenemase-producing Klebsiella pneumoniae - ALTINKANAT GELMEZ, GÜLŞEN; HASDEMİR GÖKBOĞA, MÜNEVVER UFUK (ELSEVIER, 2020)
In this study, we evaluated the performance of the two commercial methods (Rapidec Carba NP and NG-Test Carba-5) for the rapid detection of carbapenemase-producing Klebsiella pneumoniae. A total of 224 Klebsiella pneumoniae strains previously characterized for carbapenemase genes by polymerase chain reaction were included in the study. The strain collection included 30 non-carbapenemase producers, 85 OXA-48-like, 59 NDM, 14 IMP, 7 KPC, 7 VIM, 19 OXA-48-like plus NDM, and 3 KPC plus NDM producers. Rapidec Carba NP and NG-Test Carba 5 was performed according to the manufacturer's instructions. NG-Test Carba 5 correctly detected all carbapenemase-producing K. pneumoniae, however, Rapidec Carba NP failed to detect 41% of OXA-48-like producers even with extended incubation time. The overall sensitivity and specificity were 81,9% and 100% for Rapidec Carba NP, 100% and 100% for NG-Test Carba 5, respectively. Both tests seem to be fast and reliable for the detection of carbapenemase-producing K. pneumoniae especially for microbiology laboratories where molecular tests cannot be performed. However, Rapidec Carba NP with weak hydrolysis activity for OXA-48 like might be used in regions where OXA-48 is not prevalent. The additional advantage of NG-Test Carba 5 is that it specifically detects carbapenemases giving way to threat-related infections with an effective drug such as ceftazidime-avibactam or meropenem- vaborbactam.
Keywords: Rapidec Carba NP; NG-test Carba 5; Carbapenemase-producing Klebsiella pneumoniae; CARBA NP TEST; DESORPTION IONIZATION-TIME; IMMUNOCHROMATOGRAPHIC ASSAYS; PSEUDOMONAS-AERUGINOSA; ENTEROBACTERIACEAE; OXA-48; TESTS; PREVALENCE; STRATEGIES; RESISTANCE